Management of digital literacy competence development in State Madrasah Aliyah Surakarta, Indonesia - Fithriyah Nurul Hidayati; Giyoto Giyoto; Lilik Untari (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2023)
This study seeks to characterize digital literacy competency development management for educators and teaching staff at State Madrasah Aliyah in Surakarta. This study employs a qualitative descriptive methodology. Interviews, observations, and documentation studies were used to collect data. Data analysis techniques incorporated interactive analytical techniques, such as data collection, reduction, presentation, and conclusion. Method triangulation is implemented in data validity standards. According to the findings of this research project, there are three conclusions: First, the management of digital literacy competency development for educators and educational staff at Madrasah Aliyah Surakarta includes: (a) the implementation of planning with work meetings by formulating goals that are in line with the madrasah vision, mission, goals, and programs activity (b) organizing includes determining the madrasah digital literacy team's organizational structure, task distribution, and personnel. (c) the development of digital literacy competencies is implemented through informal programs and formal programs, such as workshops, training, seminars, and MGMP, which are designed to equip digital knowledge and skills, digital culture, digital ethics, and digital security. d) The Madrasah's head conducts internal evaluation and surveillance. Second, the supporting factors include assistance from the madrasah in the form of complete facilities, madrasah DIPA funds, and additional learning support in the form of scholarships that increase digital competence. Third, the nature of human resources (some educators are unaware of digital literacy, and participants are less enthusiastic about participating in development activities) hinders management development.